Implementation of comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry for the simultaneous determination of halogenated contaminants and polycyclic aromatic hydrocarbons in fish - Kalachova, Kamila; Pulkrabova, Jana; Cajka, Tomas; Drabova, Lucie; Hajslova, Jana (Analytical and bioanalytical chemistry, 2012)
In the presented study, comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC × GC-TOFMS) was shown to be a powerful tool for the simultaneous determination of various groups of contaminants including 18 polychlorinated biphenyls (PCBs), seven polybrominated diphenyl ethers (PBDEs), and 16 polycyclic aromatic hydrocarbons (PAHs). Since different groups of analytes (traditionally analyzed separately) were included into one instrumental method, significant time savings were achieved. Following the development of an integrated sample preparation procedure for an effective and rapid isolation of several groups of contaminants from fish tissue, the GC × GC-TOFMS instrumental method was optimized to obtain the best chromatographic resolution and low quantification limits (LOQs) of all target analytes in a complex mixture. Using large-volume programmable temperature vaporization, the following LOQs were achieved-PCBs, 0.01-0.25 μg/kg; PBDEs, 0.025-5 μg/kg; PAHs 0.025-0.5 μg/kg. Furthermore, several capillary column combinations (BPX5, BPX50, and Rxi-17Sil-ms in the first dimension and BPX5, BPX50, Rt-LC35, and HT8 in the second dimension) were tested during the experiments, and the optimal separation of all target analytes even of critical groups of PAHs (group (a): benz[a]anthracene, cyclopenta[cd]pyrene and chrysene; group (b): benzo[b]fluoranthene, benzo[j]fluoranthene and benzo[k]fluoranthene; group (c): dibenz[ah]anthracene, indeno[1,2,3-cd]pyrene and benzo[ghi]perylene) was observed on BPX5 × BPX50 column setup. Moreover, since the determination of target analytes was performed using TOFMS detector, further identification of other non-target compounds in real life samples was also feasible.
Keywords: látky znečišťující životní prostředí; polycyklické aromatické uhlovodíky; časové faktory; halogenované uhlovodíky; Environmental Pollutants; Animals; Fishes; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; Hydrocarbons, Halogenated; Time Factors; analýza potravin; Polycyclic Aromatic Hydrocarbons; zvířata; ryby; Food Analysis